Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing


  • 3 years ago

Nakim simplified 3 sqrt 2x + x sqrt 8x – 5 sqrt 18x and got -10x sqrt 2x for an answer. Part 1: Using complete sentences, explain what Nakim did wrong. Part 2: Show all your work to simplify the expression.

  • This Question is Closed
  1. marsss
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    sqrt(8x)=sqrt(2)*sqrt(2)*sqrt(2x)=2*sqrt(2x) sqrt(18x)=sqrt(3)*sqrt(3)*sqrt(2x)=3*sqrt(2x) so 3*sqrt(2x)+x*2*sqrt(2x)-5*3*sqrt(2x)=sqrt(2x)*(3+2x-15)=(2x-12)*sqrt(2x) so Nakim did wrong :)

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy